Chlorhexidine plus alcohol versus povidone iodine plus alcohol, combined or not with innovative devices, for prevention of short-term peripheral venous catheter infection and failure (CLEAN 3 study): an investigator-initiated, open-label, single centre, randomised-controlled, two-by-two factorial trial. Issue 7 (July 2021) - Guenezan, Jérémy; Marjanovic, Nicolas; Drugeon, Bertrand; Neill, Rodérick O; Liuu, Evelyne; Roblot, France; Palazzo, Paola; Bironneau, Vanessa; Prevost, Frederique; Paul, Julie; Pichon, Maxime; Boisson, Matthieu; et al.
Summary: Background: Two billion peripheral venous catheters are sold globally each year, but the optimal skin disinfection and types of devices are not well established. We aimed to show the superiority of disinfection with 2% chlorhexidine plus alcohol over 5% povidone iodine plus alcohol in preventing infectious complications, and of closed integrated catheters, positive displacement needleless-connectors, disinfecting caps, and single-use prefilled flush syringes used in combination (innovation group) over open catheters and three-way stopcocks for treatment administration (standard group) in preventing catheter failure. Methods: We did an open-label, randomised-controlled trial with a two-by-two factorial design, for which we enrolled adults (age ≥18 years) visiting the emergency department at the Poitiers University Hospital, France, and requiring one peripheral venous catheter before admission to the medical wards. Before catheter insertion, patients were randomly assigned (1:1:1:1) using a secure web-based random-number generator to one of four treatment groups based on skin preparation and type of devices (innovative devices or standard devices; 2% chlorhexidine plus alcohol or 5% povidone iodine plus alcohol). Primary outcomes were the incidence of infectious complications (local infection, catheter colonisation, or bloodstream infections) and time between catheter insertion and catheter failure (occlusion, dislodgment, infiltration, phlebitis, or infection). This study is registered with ClinicalTrials.gov, NCT03757143 . Findings: 1000 patients were recruited between Jan 7, and Sept 6, 2019, of whom 500 were assigned to the chlorhexidine plus alcohol group and 500 to the povidone iodine plus alcohol group (250 with innovative solutions and 250 with standard devices in each antiseptic group). No significant interaction was found between the two study interventions. Local infections occurred less frequently with chlorhexidine plus alcohol than with povidone iodine plus alcohol (0 [0%] of 496 patients vs six [1%] of 493 patients) and the same was observed for catheter colonisation (4/431 [1%] vs 70/415 [17%] catheters among the catheters cultured; adjusted subdistribution hazard ratio 0·08 [95% CI 0·02–0·18]). Median time between catheter insertion and catheter failure was longer in the innovation group compared with the standard group (50·4 [IQR 29·6–69·4] h vs 30·0 [16·6–52·6] h; p=0·0017). Minor skin reactions occurred in nine (2%) patients in the chlorhexidine plus alcohol group and seven (1%) patients in the povidone iodine plus alcohol group. Interpretation: For skin antisepsis, chlorhexidine plus alcohol provides greater protection of peripheral venous catheter-related infectious complications than does povidone iodine plus alcohol. Use of innovative devices extends the catheter complication-free dwell time. Funding: Becton Dickinson.